Length density of fine roots in teak, in a Leptic Vertisol soil in Tabasco, Mexico - Córdova-Sánchez, Alberto; Obrador-Olán, José Jesús; Castelán-Estrada, Mepivoseth; Palma-López, David Jesús; García-López, Eustolia; Villanueva-López, Gilberto; Pascual-Córdova, Guillermina (Ecosistemas y Recursos Agropecuarios, 2023)
The fine roots (≤ 2 mm in diameter) in the trees are short-lived, in conditions of drought and low fertility they reach a greater length per unit volume of soil; Thus, the root length density is a variable that indicates the water and nutrient absorption potential of the tree. The objective of this study was to estimate the fine root length density (DLRF) its distribution in depth and distance from the base of the three-year-old teak tree, due to the effect of chemical fertilization and a green manure. The methodology used was that of the cylinder, at 36 months of age of the teak trees, vertical soil samples were taken, every 10 cm up to 40 cm deep on the four faces of the profile; and at 46 months it was sampled horizontally at three distances from the base of the tree: 50, 100 and 175 cm, in a randomized complete block design. The results show that the treatments with the highest DLRF were: the 60-60-60 kg ha−1 dose without Green Manure and the control with Green Manure. The DLRF was greater at depth 20-30 cm and 10-20 cm at 38 and 46 months. At a distance of 50 cm from the base of the tree, it showed higher DLRF (0.75 km.m−3). The DLRF decreased when the chemical fertilization dose was increased or when green manure (Crotalaria juncea L.) was established.